Breaking the Cybernetic Code: Understanding and Treating the Human Metacognitive Control System to Enhance Mental Health - Wells, Adrian (Frontiers in Psychology, 2019)
The self-regulatory executive function (S-REF) model explains the role of strategic processes and metacognition in psychological disorder and was a major influence on the development of metacognitive therapy. The model identifies a universal style of perseverative negative processing termed the cognitive attentional syndrome (CAS), comprised of worry, rumination, and threat monitoring in the development of disorder. The CAS is linked to dysfunctional metacognitions that include beliefs and plans for regulating cognition. In this paper I extend the theoretical foundations necessary to support further research on mechanisms linking metacognition to cognitive regulation and effective treatment. I propose a metacognitive control system (MCS) of the S-REF that can be usefully distinguished from cognition and is comprised of multiple structures, information and processes. The MCS monitors and controls activity of the cognitive system and regulates the behaviour of neural networks whose activities bias the way cognition is experienced. Metacognitive information involved in the regulation of on-line processing includes metacognitive beliefs, metacognitive procedural commands, and more transient cybernetic code. Separation of the cognitive and metacognitive systems and modelling their relationship presents major implications concerning what should be done in therapy and how it should be done. The paper concludes with an in-depth consideration of methods that strengthen the psychological basis of psychotherapy and aid in understanding and applying metacognitive therapy in particular. Finally, limitations of the model and implications for future research on self-awareness, self-regulation and metacognition are discussed.